A History of Music Aesthetics - Fubini, Enrico (London Macmillan, 1991)
A history of music aesthetics from Antiquity to the present day. Fubini considers musical thought in terms of its relationship to philosophy, medicine, astronomy, mathematics and teaching in the period up to the Enlightenment. The second half of the book concentrates on key issues in contemporary music aesthetics, placing them in the perspective of the Enlightenment and of 19th-century philosophers. The concept of aesthetics is understood in the widest sense and the book is of interest not only to musicians but to philosophers, psychologists, physicist and mathematicians.
Keywords: Music philosophy and esthetics; Music history